Assessing the capabilities, opportunities, and motivations to implement updated Appendix A & B guidelines in small meat processors within the Mid-West - Prester, Mason J. (My University, 2025)
Food safety remains a critical concern within the meat processing industry, particularly for small meat processors who often face unique challenges due to limited resources and workforce constraints. The USDA-FSIS Appendix A & B guidelines, initially introduced in 1999, offer scientific support and procedures to enhance food safety practices, primarily targeting small processors. However, understanding how small meat processors perceive and implement these guidelines through the lens of behavior change can facilitate the development of adoptable food safety interventions. Toward this end, this study applied the COM-B model (Capability, Opportunity, Motivation, and Behavior) to assess small meat processors’ behavior toward implementing the updated guidelines across the Midwest. A previously validated 30-question survey was administered to small meat processors in Kansas, Nebraska, Oklahoma, and South Dakota, along with a one-hour training session over the updated Appendix A & B guidelines. Surveys were distributed pre-training (n = 47 respondents), post-training (n = 25 respondents), and six months post-training (n = 22 respondents). Data was analyzed using the GLIMMIX procedure of SAS with a fixed effect model for survey and state differences. The study revealed a significant increase (P < 0.05) in meat processors’ perceived capability to implement updated Appendix A & B guidelines from pre-training (3.63) to post-training (4.37) that maintained at this higher level six months post-training (4.40). However, meat processors’ perceived opportunity to implement updated Appendix A & B guidelines remained statistically unchanged across time points (P > 0.05), with an average score of 3.98 at pre-training and 3.84 six months post-training. Motivation showed a mixed response, with overall scores increasing from pre-intervention (5.13) to post-intervention (5.18) but declining at six months (4.39). State-specific analyses highlight Nebraska with the highest perceived capability (4.96) and Kansas with the lowest perceived opportunity (3.83). Motivation was influenced more by automatic rather than reflective factors, emphasizing the need for targeted interventions. The results indicate that educational interventions effectively improve perceived capability but have a limited impact on perceived opportunity and motivation. Utilizing the Behavior Change Wheel alongside the COM-B model, the study suggests that additional intervention strategies such as enablement, environmental restructuring, and incentivization could enhance behavior change. Specifically, interventions focusing on social opportunities and reflective motivation could support the sustained implementation of Appendix A & B guidelines among small meat processors. This study provides a foundational understanding of small meat processors’ behavior concerning USDA-FSIS Appendix A & B guidelines. The findings emphasize the need for tailored support from extension agents, regulatory agencies, and training programs to enhance small processors’ perceived capabilities, opportunities, and motivations. Future research should expand geographic coverage and participant numbers to create a comprehensive strategy for promoting food safety practices across the U.S. meat processing industry.
Keywords: Small meat processors; Food safety; COM-B; Appendix A; Appendix B